If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -4 + -6x + 3x + 2 = -14 Reorder the terms: -4 + 2 + X + -6x + 3x = -14 Combine like terms: -4 + 2 = -2 -2 + X + -6x + 3x = -14 Combine like terms: -6x + 3x = -3x -2 + X + -3x = -14 Solving -2 + X + -3x = -14 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + X + 2 + -3x = -14 + 2 Reorder the terms: -2 + 2 + X + -3x = -14 + 2 Combine like terms: -2 + 2 = 0 0 + X + -3x = -14 + 2 X + -3x = -14 + 2 Combine like terms: -14 + 2 = -12 X + -3x = -12 Add '3x' to each side of the equation. X + -3x + 3x = -12 + 3x Combine like terms: -3x + 3x = 0 X + 0 = -12 + 3x X = -12 + 3x Simplifying X = -12 + 3x
| -5-18=-3 | | 9/7x=20 | | x/9-7=x/2 | | 0.2x-0.6=0.4+0.8 | | x/2=5(10) | | 11d^2+7=0 | | 5x-55y=40 | | x-12=48/6 | | 3(4)=3x | | 8u-u=56 | | x-y+4z=7 | | 2/3+3k/=17/12 | | 11+13=x+1 | | X^6/6= | | 18x-6=9x+22 | | [[2b]/[7[[a]^[3]]]]smalldot;[[14[[a]^[4]]b]/[[[b]^[4]]]] | | 6m=10-8 | | 7(x+1)-5(x+2)=9 | | 21=-7/2x | | 7/9=n/180 | | 14x-12=3x+11 | | 50/4=100/x | | U+2.8=4.72 | | 8x+12=20x-18 | | 4c=6.4 | | 5x^2+11664=13689 | | 8(1+3a)+4(-6-2)=-6a+2a | | 2t+3(1-5t)= | | 7-8[9-(4y-6)]= | | 23-7=x-8 | | x+1=4x-5-x-2 | | 8x-33+7x-57=90 |